SARS-CoV-2 Surveillance in Peri-Domestic and Wildlife Species in Ontario, Canada. (March 2022) - Kotwa, J.; Sotto, A.; Yip, L.; Hou, A.; Buchanan, T.; Bowman, J.; Greenhorn, J.; Nituch, L.; Bruce, L.; Mubareka, S.
Abstract : Purpose: The rapid emergence and spread of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) has sparked concerns of spillover to naïve wildlife populations and it is unclear if wildlife could ultimately serve as a reservoir for the virus. Evidence of SARS-CoV-2 has been detected in captive and wild animals (e.g., mink, tiger, lion). Moreover, the SARS-CoV-2 variants of concern (VOCs) likely have a broader host range, suggested by the susceptibility of laboratory mice ( Mus musculus ) to the Beta and Gamma variants but not wild-type SARS-CoV-2. Peri-domestic animals (i.e., wild and feral animals living near humans) represent highly relevant species to assess spillover since they likely have a greater chance of exposure to the virus from humans. Thus, monitoring wildlife at the human-animal interface is critical in understanding the epidemiology of SARS-CoV-2. We therefore are investigating the presence of SARS-CoV-2 in key peri-domestic and wild animals across southern Ontario, Canada through a One Health framework. Methods & Materials: In collaboration with the Ministry of Natural Resources and Forestry, oral and rectal swabs are opportunistically collected from two peri-domestic species, raccoons ( Procyon lotor ) and skunks ( Mephitis mephitis ), across southern Ontario where high population densities and incidence of SARS-CoV-2 in humans likely provide spillover opportunity. Additionally, oral and rectal swab, and respiratory and intestinal tissues from trapped wild mink ( Neovison vison ) are collected in collaboration with the Ontario Fur Managers Federation. Samples are analyzed at the Sunnybrook Research Institute via a RT-qPCR for two SARS-CoV-2 gene targets: the 5' untranslated region (UTR) and the envelope gene (E). Results: From September 2020 to January 2021, 264 oral and 264 rectal swabs were collected from 207 raccoons and 57 skunks. All samples were negative for SARS-CoV-2 RNA. The study is presently ongoing. Conclusion: Based on these preliminary data, there is little evidence to suggest spillover of SARS-CoV-2 to the sampled animals during this period. Notably, these animals were sampled prior to the emergence of SARS-CoV-2 VOCs, and our results do not preclude the possibility of future spillover to wildlife at the human-animal interface. Results from ongoing surveillance efforts post-VOC emergence will also be discussed.